A State of the Art : Heat Transfer within a MOSFET System - Oussama Zobiri; Abdelmalek Atia (university Of Eloued جامعة الوادي, 2020)
The FET (field effect transistor) is the backbone of today's semiconductor electronics. The Metal Oxide Semiconductor Field Effect Transistor (MOSFET) is the most popular type of isolated gate FET used in a variety of electronic circuits. In recent years, the MOSFET miniaturization has gained considerable interest. As the size of the device decreases ( nano-scale) , the heat generated influences the efficiency of the device. There have been many thermal studies to improve the operation of the device. This paper gives an idea on the MOSFET and heat transfer phenomena within it.
Intervention
Keywords: Heat conduction; MOSFET; Nano-scale